2016
DOI: 10.1186/s40064-016-3705-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of IL-10 genetic polymorphisms with the risk of urologic cancer: a meta-analysis based on 18,415 subjects

Abstract: BackgroundInterleukin-10 (IL-10) is a powerful modulator of anti-tumor immune responses. The IL-10 promoter region polymorphisms are known to regulate IL-10 production, and thus are thought to be implicated in tumorigenesis. Recently, the roles of these polymorphisms in urologic cancer have been extensively studied, with conflicting results. Therefore, we conducted the present meta-analysis to better elucidate the correlations between IL-10 polymorphisms and urologic cancer risk.MethodsEligible articles were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Other interleukins that play a role in macrophages and neutrophils' immunosuppressive roles include IL-10, IL-12, and IL-23 [95]. Rs1800896, rs1800871, and rs1800872 in IL-10 [96] are associated with an increased risk for BC in Chinese [97] and Indian [98] populations; rs10889677 in IL-23R also increases BC risk in Chinese [99] and Polish [92] populations; and IL-12 decreases the risk in the Indian population [93]. Other interleukins were also found to play a role in BC risk; for instance, rs2069762 in the IL-2 gene increases the risk for BC in the Chinese population.…”
Section: Signalingmentioning
confidence: 99%
“…Other interleukins that play a role in macrophages and neutrophils' immunosuppressive roles include IL-10, IL-12, and IL-23 [95]. Rs1800896, rs1800871, and rs1800872 in IL-10 [96] are associated with an increased risk for BC in Chinese [97] and Indian [98] populations; rs10889677 in IL-23R also increases BC risk in Chinese [99] and Polish [92] populations; and IL-12 decreases the risk in the Indian population [93]. Other interleukins were also found to play a role in BC risk; for instance, rs2069762 in the IL-2 gene increases the risk for BC in the Chinese population.…”
Section: Signalingmentioning
confidence: 99%
“…Generally, the results of IL-10 polymorphysm studies are still confusing, ranging from no significant association 17,18,19,20,21,22,23,24 to association of particular alleles in CP patients 15,25,26,27,28,29,30,31,32,33,34,35,36 . Several of these studies that confirmed association of particular IL-10 polymorphism with CP reported also a significant correlation of GG-1082 gene alleles with low grade tumors 18,26,28,32,34,37 , absence of bone metastasis 30 or low reccurence rate 31 .…”
Section: Radiation Therapy Induce Average Il-10 Increase In Serummentioning
confidence: 99%